REFORMS ARE ONGOING IN THE HIGHER EDUCATION SYSTEM - Sh.I. Nizamova (Journal of Learning on History and Social Sciences, 2024)
This article discusses the reforms carried out in the higher education system, practical work in improving the quality of education, and the knowledge necessary for training future specialists. Information is provided about the social necessity of teaching the science of educational management, the integration of the preparation of students for professional activity with educational management. The opinions of the representatives of management are presented.